Association of myosteatosis with various body composition abnormalities and longer length of hospitalization in patients with decompensated cirrhosis - Wang, Xiaoyu; Sun, Mingyu; Li, Yifan; Guo, Gaoyue; Yang, Wanting; Mao, Lihong; Yu, Zihan; Hui, Yangyang; Fan, Xiaofei; Cui, Binxin; Jiang, Kui; Sun, Chao (Frontiers in Nutrition, 2022)
Background Myosteatosis is linked to dismal outcomes in the context of cirrhosis. However, the association of myosteatosis with various body composition abnormalities remains enigmatic. We aimed to clarify the determinants of myosteatosis and its relationship with other body composition profiles and length of hospitalization (LOH). Methods We retrospectively analyzed the data of 473 consecutive patients with cirrhosis hospitalized for decompensation. Computed tomography-based segmentation of the cross-sectional area at the third lumbar vertebra was used to evaluate body composition abnormalities. The categories of myosteatosis were built according to our previously outcome-based cutoffs for each gender. Results Totally, 83 patients (17.55%) were stratified as myosteatosis, of whom 85.54% had concomitant high visceral adiposity indicative of increased visceral adipose tissue index (VATI). The prevalence of sarcopenia showed no significant difference between the groups with and without myosteatosis. Multivariate analysis showed that advanced age [odds ratio (OR) = 1.097, p < 0.001], higher visceral to subcutaneous ratio of adipose tissue area (VSR; OR = 1.574, p = 0.032), and higher VATI (OR = 1.026, p < 0.001) are independently associated with myosteatosis. Correlation analyses revealed a positive relationship between intramuscular adipose tissue content (IMAC) and VATI (ρ = 0.48, p < 0.001), subcutaneous adipose tissue index (SATI) (ρ = 0.36, p < 0.001), and age (ρ = 0.36, p < 0.001). None of the skeletal muscle or adipose tissue indicators were significantly related to longer LOH. Conclusion Higher VSR, higher VATI, and advanced age are associated with myosteatosis among patients with cirrhosis at the decompensation phase. It is tempting to target divergent adipose tissue depots aimed at timely intervention/prevention of myosteatosis.